TAJAM KE BAWAH TUMPUL KE ATAS - Amrunsyah Amrunsyah (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2017)
The Criminal Law is part of the national legal system that has been in effect since independence until now. Implementation of criminal law finds ups and downs as the development of society is even a keen spotlight when it has not provided justice and welfare and is still regarded as an instrument of power to protect state officials and become a weapon for the common people when against the state. Implementation of criminal law in Indonesia aims to provide protection, tranquility, order and legal certainty to the community. Although there are objectives that provide protection, especially personal or individual interests in exercising the rights of citizens. While the purpose of this paper is to provide an understanding that the Criminal Law is a chain of legislation applicable in Indonesia and its content is focused on the Criminal Code and Criminal Procedure that reach all levels of society.